Choreography and Verbatim Theatre Dancing Words - McCormack, Jess (Springer International Publishing, 2018)
How might spoken words be translated into choreography? This book addresses the field of verbatim dance-theatre, around which there is currently limited existing scholarly writing. Grounded in extensive research, the project combines dance studies and performance studies theory, detailed analysis of professional choreographic work and examples of experimental practice to then employ the framework of translation studies in order to consider what a focus on movement and an attempt to dance/move other people's words can offer to the field of verbatim theatre. It investigates ways to understand, articulate and engage in the process of choreographing movement as a response to verbatim spoken language. It is directed at an international audience of dance studies scholars, theatre and performance studies scholars and dance-theatre practitioners, and it would be appropriate reading material for undergraduate students seeking to develop their understanding of choreographic processes that use written/spoken text as a starting point and graduate students working in the area of adaptation, verbatim theatre, physical theatre or devised theatre.